Statistical learning and language acquisition - Williams, John N. (De Gruyter Mouton, 2012)
This volume brings together contributors from cognitive psychology, theoretical and applied linguistics, as well as computer science, in order to assess the progress and future directions of statistical learning research. The textcritically examines the role of statistical learning in language acquisition. Contributors agree that statistical learning plays a central role in language acquisition, but each offerdiffering perspectives. The book promotes the development of the field by fostering discussion and collaborations across disciplinary boundaries.
Description based on print version record.
Keywords: Linguistics -- Statistical methods.; Psycholinguistics.; Theoretical linguistics.; Applied linguistics.; Language acquisition.; Psycholinguistics; Language Development; Linguistique -- Méthodes statistiques.; Psycholinguistique.; Linguistique appliquée.; Langage -- Acquisition.; psycholinguistics.; applied linguistics.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Psycholinguistics.; Linguistics -- Statistical methods; Applied linguistics; Language acquisition; Applied Linguistics, Language Acquisition, Education.; Electronic book.